2002
DOI: 10.2139/ssrn.362840
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Statistical Life: A Critical Review of Market Estimates throughout the World

Abstract: A substantial literature over the past thirty years has evaluated tradeoffs between money and fatality risks. These values in turn serve as estimates of the value of a statistical life.This article reviews more than 60 studies of mortality risk premiums from ten countries and approximately 40 studies that present estimates of injury risk premiums. This critical review examines a variety of econometric issues, the role of unionization in risk premiums, and the effects of age on the value of a statistical life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
462
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(481 citation statements)
references
References 95 publications
13
462
3
3
Order By: Relevance
“…The earlier estimate was itself an inflation-adjusted update of EPA’s earlier assumption of $4.8 million in 1990 dollars. All these figures fit within the relatively wide range of $4 to $9 million implied by U.S. labor market data on wage differentials associated with mortality risks (Viscusi and Aldy, 2003). …”
Section: Estimating the Economic Costs Of War-related Injury And Dsupporting
confidence: 66%
See 2 more Smart Citations
“…The earlier estimate was itself an inflation-adjusted update of EPA’s earlier assumption of $4.8 million in 1990 dollars. All these figures fit within the relatively wide range of $4 to $9 million implied by U.S. labor market data on wage differentials associated with mortality risks (Viscusi and Aldy, 2003). …”
Section: Estimating the Economic Costs Of War-related Injury And Dsupporting
confidence: 66%
“…The loss of a limb, for example, reduces future earnings but also probably reduces enjoyment of leisure activities, a harm that would persist even after lost earnings were recouped. In modern periods, estimates of the willingness to pay to avoid death or a particular injury, called the value of a statistical life (VSL) and the value of a statistical injury (VSI), are much larger than is implied by the capitalized value of lost future wages (Viscusi, 1993; Viscusi and Aldy, 2003). From this perspective, the economic costs of deaths and injuries depend on the VSL and VSI.…”
Section: Estimating the Economic Costs Of War-related Injury And Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The human capital approach (HCA) takes an ‘employee perspective’ and estimates the productivity losses over an expected working lifetime, irrespective of whether an individual dies from the risk factor and/or an employer can replace the worker 13. Finally, a value of a statistical life (VSL) approach monetises an average or ‘statistical’ life lost 14. The key difference of a VSL approach is that it seeks to value life lost as opposed to estimating the productivity costs incurred.…”
Section: Methodsmentioning
confidence: 99%
“…We adjusted the value of a DALY to reflect the expected below-average lifetime income of AHT victims had they not been victimized. Specifically, we adjusted the estimates using an income elasticity of 0.47 from Viscusi and Aldy (2003), as recommended by Hammitt and Robinson (2011). Following guidelines from the Second Panel on Cost-Effectiveness in Health and Medicine (Neumann et al 2016), we showed work and DALY losses separately.…”
Section: Methodsmentioning
confidence: 99%